2008
DOI: 10.1007/s11250-008-9230-6
|View full text |Cite
|
Sign up to set email alerts
|

Feed intake, digestibility, body weight and carcass parameters of Afar rams fed tef (Eragrostis tef) straw supplemented with graded levels of concentrate mix

Abstract: The experiment was conducted at Alamata Agricultural Research Center, Ethiopia using 20 Afar rams with an initial body weight (BW) of 18.2 +/- 1.76 (mean +/- SD) kg. The objectives were to study the effect of supplementation with concentrate mix consisting of wheat bran (WB), noug seed cake (NSC) and sesame seed cake (SSC) at the ratio of 2:1:1 on dry matter (DM) basis, respectively on feed intake, digestibility, BW gain and carcass parameters of Afar rams fed tef (Eragrostis tef) straw basal diet. The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
13
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 15 publications
(23 reference statements)
9
13
6
Order By: Relevance
“…The CP content of DMLM in this study was comparable with previously reported values of 201 g/kg DM (Kandylis et al, 2009) and 203 g/kg DM (Vu et al, 2011). The CP content of WB in the present study was similar with values of 168 g/kg DM (Tolera, 2008) and 168.2 g/kg DM (Hagos and Melaku, 2009). The CP content of NSC in the present study was comparable to value of 331 g/kg DM noted in earlier study (Abraham et al, 2015).…”
Section: Chemical Composition Of Experimental Feedssupporting
confidence: 91%
“…The CP content of DMLM in this study was comparable with previously reported values of 201 g/kg DM (Kandylis et al, 2009) and 203 g/kg DM (Vu et al, 2011). The CP content of WB in the present study was similar with values of 168 g/kg DM (Tolera, 2008) and 168.2 g/kg DM (Hagos and Melaku, 2009). The CP content of NSC in the present study was comparable to value of 331 g/kg DM noted in earlier study (Abraham et al, 2015).…”
Section: Chemical Composition Of Experimental Feedssupporting
confidence: 91%
“…In line with the present study, Hagos and Melaku (2009) and Abebaw and Solomon (2008) found that sheep supplemented with good protein source showed better daily gain and fi nal BW.…”
Section: As Illustrated Insupporting
confidence: 91%
“…In the current study, the average daily BW gain in the supplemented sheep were comparable with 43.3 -67.1 g/head/day reported in Afar rams supplemented with sole noug seed cake, wheat bran , sesame seed cake and their mixture (Hagos and Melaku, 2009). …”
Section: As Illustrated Insupporting
confidence: 86%
See 2 more Smart Citations